2020
DOI: 10.1080/01434632.2020.1749643
|View full text |Cite
|
Sign up to set email alerts
|

Closer to far away: transcending the spatial in transnational families’ online video calling

Abstract: This paper studies how transnational children and their distantly located but emotionally close family members recreate their relationship using applications for online video calling. The focus is on the interaction of bodies and language, and if/how proximity of any kind is enabled. A critical posthumanist applied linguistics is embraced and communication is viewed as a bodily coordination ocurring in real time. This includes a material and dynamic view of language in constant transformation. Video captures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This finding is supported by different findings of previous studies about how employees value staying in contact and how video technology can make this possible (Patton and Doherty 2020). Multiple studies have shown that individuals primarily use communication technologies to interact with family about their well-being, life advice, economic support, and general everyday activities (Gan 2021;Kędra 2020;Martín-Bylund and Stenliden 2020). Similarly, the findings of the current study highlight the importance of participants communicating with family members through video technology as a way to update loved ones about their well-being and day-to-day activities that might make it seem that they are close to each other despite the distance.…”
Section: Discussion Of Findingssupporting
confidence: 57%
See 3 more Smart Citations
“…This finding is supported by different findings of previous studies about how employees value staying in contact and how video technology can make this possible (Patton and Doherty 2020). Multiple studies have shown that individuals primarily use communication technologies to interact with family about their well-being, life advice, economic support, and general everyday activities (Gan 2021;Kędra 2020;Martín-Bylund and Stenliden 2020). Similarly, the findings of the current study highlight the importance of participants communicating with family members through video technology as a way to update loved ones about their well-being and day-to-day activities that might make it seem that they are close to each other despite the distance.…”
Section: Discussion Of Findingssupporting
confidence: 57%
“…These findings extend the current literature about the use of video technologies. Previous research has shown how families build relationships using video chat (Gan 2021;Kędra 2020;Martín-Bylund and Stenliden 2020). The topic of families building relationships using video chat, particularly those with young children who are living away from other family members, has been explored (Gan 2021;Kędra 2020;Martín-Bylund and Stenliden 2020), including how it allows for more authentic reactions and emotions to be shared surrounding such events, as emotions and thoughts about an event can be shared as they are cognitively formed instead of being recalled after the fact (Gan 2021;Kędra 2020;Martín-Bylund and Stenliden 2020).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations